Adjuvant chemotherapy compared with observation in patients with resected biliary tract cancer: A systematic review and meta-analysis of randomized controlled trials - Liying Tian; Qian Guo; Daidi Fu; Xiao Ma; Linjun Wang (PLoS ONE, 2025)
Objectives Several randomized controlled trials compared adjuvant systemic chemotherapy with observation in patients with resected biliary tract cancer (BTC) have yielded inconsistent outcomes. In order to assess the efficacy of adjuvant therapy in these patients, we conducted this systematic review and meta-analysis. Methods We conducted a thorough search in various databases, which included MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, ASCO Abstracts, ESMO Abstracts and ClinicalTrials.gov. All relevant randomized controlled trials investigating the adjuvant chemotherapy compared with observation in resected biliary tract cancer were identified. The primary outcome of interest was overall survival (OS), while secondary outcome was relapse-free survival (RFS). Statistical analyses were conducted using Review Manager 5.3. Additionally, publication bias was evaluated using Egger’s test in Stata 12.0. Results A total of 5 randomized controlled trials, involving 1406 patients, were included in this analysis. Compared with observation, adjuvant chemotherapy improved RFS [HR 0.84 (0.73-0.96), p=0.01] (I2=0%, p=0.89) but not OS [HR 0.89 (0.77-1.03), p=0.12] (I2=51%, p=0.09) in the entire population after BTC resection. Subgroup analyses revealed that adjuvant chemotherapy did improve both OS [HR 0.76 (0.62-0.93), p=0.009] (I2=7%, p=0.37) and RFS [HR 0.74 (0.58-0.95), p=0.02] (I2=0%, p=0.39) in patients with lymph node positivity. Furthermore, patients receiving oral fluoropyrimidine monotherapy showed benefit from the adjuvant therapy, with longer OS [HR 0.78 (0.65-0.94), p=0.009] (I2=2%, p=0.31) and RFS [HR 0.81 (0.68-0.95), p=0.01] (I2=0%, p=0.95). Conclusions To conclude, adjuvant chemotherapy have the potential to offer advantages in patients with resected BTC. Specifically, patients demonstrating positive lymph node status have a higher likelihood of benefiting from adjuvant therapy. Our analysis supports the current standard of care of adjuvant fluoropyrimidine. However, the recommendation of oral fluoropyrimidine monotherapy as the preferred option is not definitive, as it is based on limited studies. Further validation of these outcomes is necessary by conducting extensive randomized controlled trials.